Characteristics Of Peatland Chemical Properties Due To Differences In Land Use In Muara Sugihan District Banyuasin Regency South Sumatra Province - Syahrin adi putra; Parwi Parwi; Use Etica (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2026)
Purpose : This study aims to analyze the characteristics of peat soil chemical properties due to differences in land use and differences in depth in Muara Sugihan District, Banyuasin Regency, South Sumatra. Methodology : Determination of sampling points using the purposive sampling method, soil sampling using the composite method, and the samples were analyzed in the Agrotechnology Unida Gontor laboratory. Soil samples were collected from several land-use types, namely agriculture, plantations, and natural forests. Soil pH analysis was carried out using 1 N KCl solution, The Walkley and Black method determined organic carbon, Total nitrogen was analyzed using the Kjeldahl method, Available phosphorus was analyzed using Bray I, exchangeable potassium was analyzed using 1 N NH4 Acetate extraction pH 7 and measured with a flame photometer, Cation exchange capacity using the 1N NH4 Acetate Extract method on basic cations, and base saturation is the result of base cations and exchangeable potassium, while organic acids were analyzed using the spectrophotometric method. Results : The results of laboratory analysis show that the conversion of forest land into agricultural land shows better prospects than the conversion into plantation land. Findings : Higher organic matter content in agricultural land is crucial for long-term sustainability and as a foundation for soil fertility. Conclusion. Differences in the depth pattern of the topsoil (0-30) cm and subsoil (30-60) layers also indicate that agricultural practices such as tillage, crop rotation, and the application of organic matter can distribute nutrients more evenly in the soil profile. This article is an article resulting from research on the chemical analysis of peatland in Muara Sugihan District, Banyuasin Regency, South Sumatra. Type of Paper: Research article.